CULINARY MSME CONSUMERS’ ATTITUDE TOWARD HALAL LABEL: ITS EFFECT ON PURCHASING DECISION - Mahir Pradana; Budi Rustandi Kartawinata; Dyah Maharani; Mahendra Fakhri; Hiendra Kurniawan (Fakultas Seni Rupa dan Desain ITB, 2021)
This research is a study on halal consumer behavior, which consists of empirical results from various Micro, Small, and Medium Enterprises (MSME)s in Bandung, Indonesia. Data were collected from 161 muslim tourists who have experiences visiting Bandung, West Java, Indonesia, and consuming culinary products produced by MSMEs in the city. Simple linear regression method was applied to evaluate the relation between consumers’ attitude and purchase decisions. This research aims to provide deeper understanding on the effect of tourists’ attitude towards the halal label and purchase decision, seen from the perspective of muslim consumers who have experiences in consuming the food products by Micro, Small, and Medium Enterprises (MSME)s in Bandung, Indonesia. This study reveals that attitude towards halal label is an important factor affecting consumers’ halal food purchase decision.